2018
DOI: 10.1002/mus.26158
|View full text |Cite
|
Sign up to set email alerts
|

Distal Predominance of Electrodiagnostic Abnormalities in Early‐Stage Amyotrophic Lateral Sclerosis

Abstract: EMG abnormalities are predominant in the distal limb in early-stage ALS. A redefinition of an EDX-positive cervical or lumbosacral segment, with an emphasis on distal limb muscles, may result in an earlier ALS diagnosis. Muscle Nerve 58: 389-395, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Srinivasan et al found that 11 of the 34 patients undergoing surgery for their symptoms had a pre-operative EMG and that of nine reports available for review, eight indicated evidence of polyradiculopathy and none mentioned the possibility of motor neuron disease (MND) [30]. This may be related to the findings of Shayya et al that EMG diagnostic sensitivities are lowest in patients categorized as possible ALS, intermediate in patients with probable and probable with laboratory support ALS, and highest in those with definite ALS [34]. Furthermore, these studies highlight the importance of a well-trained and experienced electrophysiologist performing the study and interpreting the data.…”
Section: Role Of Electrodiagnosis and Neuroimaging In Diagnostic Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…Srinivasan et al found that 11 of the 34 patients undergoing surgery for their symptoms had a pre-operative EMG and that of nine reports available for review, eight indicated evidence of polyradiculopathy and none mentioned the possibility of motor neuron disease (MND) [30]. This may be related to the findings of Shayya et al that EMG diagnostic sensitivities are lowest in patients categorized as possible ALS, intermediate in patients with probable and probable with laboratory support ALS, and highest in those with definite ALS [34]. Furthermore, these studies highlight the importance of a well-trained and experienced electrophysiologist performing the study and interpreting the data.…”
Section: Role Of Electrodiagnosis and Neuroimaging In Diagnostic Delaymentioning
confidence: 99%
“…However, the 2006 Awaji-Shima criteria determined that fasciculation potentials (without positive sharp wave or fibrillation potentials) in the presence of chronic motor axon loss sufficiently represented LMN degeneration, allowing for earlier diagnosis and classification. These criteria have been shown to increase the sensitivity of diagnosis in ALS [34] and have equal specificity when compared to the revised El Escorial criteria [35]. Multiple studies have highlighted the important role of neurophysiological testing in the form of EMG and NCS.…”
Section: Role Of Electrodiagnosis and Neuroimaging In Diagnostic Delaymentioning
confidence: 99%
“…In our cohort, all participants had arm weakness while only half experienced leg weakness at the time of scan. Another reason may be the hypothesized selective motor neuron vulnerability in the cervical enlargement region, which is supported by clinical and electrodiagnostic studies showing non-contiguous and preferential limb muscle involvement in ALS ( Babu et al, 2017 , Shayya et al, 2018 , Nijssen et al, 2017 ). It has been hypothesized that regional differences in motor neuron density, metabolic energy demands, glial activation abnormalities, etc., may explain preferential lower motor neuron vulnerability in different cord regions ( Nijssen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…The 2006 Awaji-Shima criteria now permits fasciculation potentials (without need for positive sharp waves or fibrillation potentials) in the presence of chronic motor axon loss changes as adequate evidence of lower motor neuron degeneration, allowing for earlier diagnosis and classification. Furthermore, these Awaji-Shima criteria exhibit increased sensitivity (43) and equal specificity of an ALS diagnosis when compared to the revised El Escorial criteria (44). In a study by Palese et al, EDX was the most common first investigatory procedure in the pathway to the ALS diagnosis, followed by brain and spinal cord imaging (38).…”
Section: Role Of Electrodiagnosis and Neuroimaging In Diagnostic Delaymentioning
confidence: 99%
“…Of course, the use of EDX testing does not guarantee a correct diagnosis. Evidence suggests EDX diagnostic sensitivities are lowest in patients categorized as possible ALS and intermediate in patients with probable and probable with laboratory support ALS; the highest sensitivities were found in those with definite ALS (43). In addition, other neuromuscular diseases such as multifocal motor neuropathy or Lambert-Eaton myasthenic syndrome may require a neurologist with a higher degree of expertise in EDX to collect and interpret the data in order to distinguish diseases such as these from ALS.…”
Section: Role Of Electrodiagnosis and Neuroimaging In Diagnostic Delaymentioning
confidence: 99%